INCREASING TEACHERS' CAPABILITIES IN DISTANCE LEARNING USING THE GOOGLE CLASSROOM APPLICATION THROUGH PERSONAL ASSISTANCE OF TEACHERS IN KEMPONG KALIBAWANG, KULON PROGO DISTRICT, 2020/2021 - Dwi Wahyuni (International Journal of Chemistry Education Research, 2021)
This research is motivated by teachers who are still not ready to face distance learning during the Covid-19 pandemic. To overcome this problem researchers take corrective actions through school action research which aims to improve the ability of teachers and researchers to provide personal assistance using the Google Classroom application program for learning. distance and improve school performance in order to be able to compete in the field of graduation. The research design uses a qualitative design, while the data collection technique uses the method of documentation and observation. The data analysis technique was carried out through a qualitative descriptive model consisting of data reduction, data presentation, and drawing conclusions. The results of this study can be seen from the increase in the results of the ability of the participants in personal assistance and the implementation of activities by resource persons from before the action in cycles I and II. In the pre-cycle of participants who got an average score of 3.52, the percentage was 88.04% with the "Very Good" category, there was 1 person while the average score was 3.12, the percentage was 78.12%, the conversion value reached 3, the next 6 participants got a score of 2, the category "Quite Good". Based on the teacher's ability in the first cycle it reached 74.65% if converted the value obtained 3, with the "Good" category while in the second cycle it reached 87.49%, if the conversion value obtained a value of 4, with the "Very Good" category. Based on the implementation of mentoring by the resource persons in the first cycle, it reached 87.46%, if converted the value obtained 4, with the "Very Satisfactory" category while in the second cycle it reached 91.22% if converted the value obtained 4, with the "Very Satisfactory" category